Social Pressure in The Quarter Life Crisis Through Poster Media - Uly, Adinda Tiarani Dania; Mulmaijah, An Nur Ghamiyyu; Nugrananda, Arya; Dhiaulhaq, Dhiaulhaq; Rahayu, Erni Dwi; Mauliddina, Niar Eka; Sheikh Abdullah, Siti Rozaimah (Tarqabin Nusantara Group, 2023)
Quarter Life Crisis is a time when a person experiences confusion, uncertainty and stress which is often experienced by individuals in their 20s to early 30s. One cause is social pressure. The characteristics of someone experiencing a quarter life crisis include, the individual does not know what his desires and goals in life are, his achievements at that age do not match expectations, he is afraid of failure, he does not want his childhood and adolescence to fail. This community empowerment activity is carried out online via Instagram Post from the @phoffeedu account. This activity aims to provide education to Instagram followers @phoffeedu and people who are within Instagram's reach through the hashtag (#) displayed on posts, explore, stories, etc. Regarding the definition, characteristics and methods of preventing and managing quarter life crisis, social media can be used to share health information so that it is effective in changing people's behavior. One of the health promotion media is posters. The theme of this poster is Social Pressure in the Quarter Life Crisis. 50 hours since the poster was uploaded, it has received approximately 147 likes. Of the 41 comments submitted on the poster, 100% of them showed positive reactions from the audience. There were also those who said that the poster really helped them, especially generation Z, in preparing for, preventing or overcoming a quarter life crisis. This means that the goal of the post to raise awareness about the quarter-life crisis has been achieved according to the comments.